Effects of Different Fertilization on Soil Quality and Tomato Crop (Lycopersicon Esculentum Mill.) - Punhoon Khan Korai; Dost Jan; Ammar Rasheed; Shahmir Ali Kalhoro; Naimatullah Koondhar; Shah Mohammad; Fareea Khalil; Aidah Baloch (Dialogue Social Science Review (DSSR), 2025)
The study's goal was to examine "effects of different fertilization on soil quality and tomato crop (Lycopersicon esculentum Mill.)" during the kharif 2021 growing season. Treatments for nitrogen and potassium fertilizers among the alternatives were 0-0 kg ha-1, 50-30 kg ha-1, 70-40 kg ha-1, 90-50 kg ha-1, 110-60 kg ha-1, and 130-70 kg ha-1. Randomized complete block designs were used set up the experiment with three replications. In this trial, the tomato was assessed for soil quality, numerous growth, yield, and fruit quality. Different amounts of NK fertilizers had a significant impact on all soil quality, fruit quality, and productivity (P<0.05). Nitrogen (N) and Potassium (K) fertilizers applications were applied @130-70 kg ha-1 NK fertilizers and 110-60 kg ha-1 NK fertilizers, with comparable the soil pH, soil EC (dSm-1), total nitrogen (%), available phosphorus, and available potassium of the tomato soil were all calculated, as well as the number of branches plant-1, days to flowering, days to fruiting, number of fruits plant-1, single fruit weight (g), yield plot-1 (kg), and yield ha-1 (tons). The crop applied with the most NK fertilizers (130-70 kg ha-1) produced the high soil pH (8.04), soil EC (1.54 dSm-1), total nitrogen (%) (0.42), available phosphorus (4.17), available potassium (120.94), followed by crops with (110-60 kg ha-1) NK fertilizers produced soil pH (7.98), soil EC (1.38 dSm-1), total nitrogen (%) (0.41), available phosphorus (4.14), available potassium (120.50), while the lowest soil pH (7.64), soil EC (0.88 dSm-1), total nitrogen (%) (0.25), available phosphorus (4.017), available potassium (119.61) produced in no fertilizers (0-0) application, respectively. The crop fertilized with (130-70 kg ha-1) produced the largest single fruit weight (56.57 g), followed by crops grown with the least NK fertilizer (110-60, 90-50 and 70-40 kg ha-1) producing 54.40, 50.067, and 49.833 (g), respectively. The crop fertilized (130-70 kg ha-1) NK fertilizers, the most yield ha-1 (15.20 tons), followed by crops with 110-60 kg ha-1, 90-50 kg ha-1, and 70-40 kg ha-1, which produced 15.133, 14.067, and 13.57 tons, respectively. The tomato soil quality, crop growth, and yield were somewhat greater in crops fertilized using NK fertilizers levels of 130-70 kg ha-1, however, there are distinctions between quantitative and qualitative data attributes when they were compared, they were non-significant to crops treated with NK fertilizers at the rate of 110-60 kg ha-1 is lower. As a result, an optimal level of NK fertilizers concentrations of 110-60 kg ha-1 were established to produce economically superior soil quality and tomato fruit yield quality.